2011
DOI: 10.1111/j.1365-2842.2010.02195.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of temporomandibular disorder symptoms: a 3-year cohort study of university students

Abstract: The aims of this study were to examine the incidence of temporomandibular disorders (TMDs) over a 3-year period and to evaluate the risk of self-reported TMDs among university students in Japan. The study population comprised 2374 university students examined at the start of their undergraduate course and 492 students re-examined after 3 years using questionnaires on symptoms of TMD and experiences of jaw injury, stress, orthodontic treatment and parafunctional habits. Cumulative incidence (%) and relative ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
1
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 32 publications
6
36
1
8
Order By: Relevance
“…These results support earlier findings showing that psychosocial factors such as depression and stress associate with facial pain. [25][26][27] . Akhter et al 25 discovered in their study from 492 Japanese university students that stress, traumas, and bruxism associate significantly with TMD in a three-year follow-up period.…”
Section: Discussionmentioning
confidence: 98%
“…These results support earlier findings showing that psychosocial factors such as depression and stress associate with facial pain. [25][26][27] . Akhter et al 25 discovered in their study from 492 Japanese university students that stress, traumas, and bruxism associate significantly with TMD in a three-year follow-up period.…”
Section: Discussionmentioning
confidence: 98%
“…The prevalence was higher than that in the general population [1,2]. Since psychological stress was associated with TMJ clicking [13] and junior hospital dentists of the oral surgery specialty sustained larger stress [36], the high percentage of such a manifestation among the first-year dental residents at the Department of Oral and Maxillofacial Surgery is anticipatable.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological papers have demonstrated a relationship between occurrence of TMJ clicking and psychological stress [13], impaired masticatory functions [2], parafunctions [13,14] as well as dental caries [14]. A cephalometric study has found a shorter sagittal midface amongst those patients who displayed the joint sound [15].…”
Section: Introductionmentioning
confidence: 99%
“…dental occlusion and bruxism), 10,11 psychological factors, like stress 11 and depression, 12 have also been related to TMD, especially chronic TMD conditions. It is well-reported that a considerable number of TMD patients are clinically depressed, and this depression may influence their response to conventional therapies.…”
Section: Discussionmentioning
confidence: 99%